The Relationship of Some Immediate Chemo-Chemical Variables after the Aerobic Physical Increasing Effort for Football Players (Medico Legal Update, 2021)
In order to study some biochemical variables on the increasing aerobic physical stress-test, the researchersselected a sample of individuals represented by the Anbar University football team of 16 players who underwentthis study. The researchers used the descriptive approach in their research. The research experiment includedtaking blood samples before and after the escalating physical exertion on the Treadmill device in order toknow the effect of this effort on some biochemical variables (cholesterol, white blood cells, lactic acid).Theyconducted aerobic increasing physical effort stress-test on a Treadmill device which has an impact on thetargeted Chemo-chemical variables and the existence of correlative relationships between those variables.The researchers concluded that there are significant changes in these variables in favor of the post-testmeasurements, as well as obtaining significant correlation coefficients between these three biochemicalvariables. Then the researchers recommended the necessity of conducting studies in the same regard tothe rest of the other difference games and the need to study other variables and recognize the correlationsbetween those variables. To design curricula Modern training according to scientific foundations to enhancethe positive correlation between the variables that were discussed and reduce the relative difference betweenthe variables whose relations have gone in the negative direction and that negatively affects the physicalachievement.